The protection of minority shareholders in South Africa: a reflection on the derivative action, appraisal rights and oppression remedy - Mhembere, Tarisai Valerie (Department of Commercial Law, 2020)
This thesis will be conducted by reviewing South African literature that is published in various primary and secondary sources. The research will refer to key South African statutes namely, the South African Companies Act, the Constitution of the Republic of South Africa, 1996 (hereafter referred to as the Constitution) and the Promotion of Access to Information Act 2 of 2000. Parallel statutes of Zimbabwe, Canada, and the United States of America will also be referenced throughout this thesis. Additionally, this thesis will review case law relating to the subject and the ratio of those cases will be analysed. The role of the courts in interpreting certain legal provisions will be important in assessing whether the courts have adopted a liberal or restrictive approach to the issue of protecting minority shareholders. A comparative analysis will be conducted to evaluate how South African company law has dealt with the issue of the protection of minority shareholders. This thesis will therefore compare and contrast South African and Zimbabwean legislation and case law on minority shareholder remedies. This will be achieved by evaluating how the two nations implement and apply legislation providing for the protection of minority shareholders. As part of this analysis, this thesis will review what Zimbabwe can learn from the South African system.